ID-based proxy re-signcryption scheme - Wang Huige; Wang Caifen; Cao Hao (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
Combining the idea of signcryption, a proxy re-signcryption scheme based on identity is proposed. This scheme is a primitive that allows a semi-trusted entity called the "proxy" to convert the signcryption addressed to a "delegator" to those that can be de-signcrypted by a "delegatee", by using some special information given by the delegator, called "rekey". In the scheme, the proxy is not allowed to know the secret keys of the delegator or the delegatee, or the plaintext during the conversion. The proxy and delegatee, however, are not allowed to collude with each other. Compared to the existing scheme, the proxy re-signcryption proposed by us implements the full conversion-a signcryption under the keys for two parties can be transferred to another signcryption under another different two keys, and the verification of the signcryption can be progressed without the participation of plaintext. Meanwhile, the security of the scheme is proved under the ROM. Finally, we give the analysis of the efficiency, performance and the function of the scheme, which proves that the function of our scheme is stronger and more perfect than that of the existing schemes.